Correlation of geriatric assessment and outcomes of acute myeloid leukemia in elderly patients - El Razzaz Mostafa Kamal; Ahmed Tamer Mohamed; Magdy Hebatullah; Dawod Ramadan Eid; Mansour Basma Saeid (Forum of Clinical Oncology)
Frailty is a vulnerable susceptibility to stressors during aging. Assessment of frailty could help make appropriate management plans and early interventions. Geriatric 8 (G8) is a screening tool designed to identify those at risk for frailty who need a more detailed assessment, while Geriatric Assessment in Hematology (GAH) is a multidimensional assessment similar to the comprehensive assessment designed specifically for patients with hematological malignancies.